Augmented Reality Implementation in Financial Regulatory Education for Indonesian High School Students - Permana Putri, Dian; Nisa Febianti, Yopi; Herawan, Endang (JTP - Jurnal Teknologi Pendidikan, 2025)
Financial Services Authority (OJK) education among Indonesian tenth-grade students. Using a mixed-methods research and development approach with the ADDIE model, the study involved 40 students selected through purposive sampling for needs assessment incorporating Technology Acceptance Model constructs. An Android-based AR application was developed using Unity 3D engine and ARCore SDK, integrating interactive 3D visualizations with comprehensive OJK educational content. Expert validation was conducted by content and design specialists using structured evaluation rubrics. The needs assessment revealed strong student support for AR integration, with 67.5% expressing positive attitudes toward AR-based learning materials. A significant positive correlation (r = 0.734, p < 0.01) was found between media diversification and learning motivation. Technology readiness showed high perceived usefulness (M = 4.2, SD = 0.8) but moderate perceived ease of use (M = 3.1, SD = 0.9). Expert validation demonstrated high content validity (87.5%, CVI = 0.875) and acceptable design quality (77.8%, DQI = 0.778). The application successfully integrated four main OJK content modules with AR functionality, including interactive 3D organizational structure visualization. Findings provide strong empirical support for AR technology adoption in financial literacy education, validating constructivist and multimedia learning theories. The study establishes a replicable framework for AR educational material development, supporting continued educational technology innovation.